Flexural Strength Performance of Glass Fibre Reinforced Concrete (GFRC) Beam With Bottom Ash as Fine Aggregate Replacement - Nurharniza, Abdul Rahman; Chua, Kathy; Kishan, Gunasegaran; Lee, Hoong Pin; Low, Wen Pei (INTI International University, 2022)
Today, there are numerous newly invented concretes produced involving material replacement. Most of the new products prefer natural aggregates or cement waste material for a more sustainable and economical design. In line with these objectives, this project used glass fibre as part of material replacement in plain concrete in order to enhance concrete properties. The presence of glass fibre may help to reduce cracks and at the same time may help to increase the strength of concrete. This condition may help to produce higher flexural strength when the concrete is used in a concrete structure. As the new direction of concrete innovation work is now looking forward on engineered composite concrete (ECC) which had go towards the invention of a composite concrete, thus this project had also used bottom ash as fine aggregate replacement. This may help to minimize the environmental burden and reduce construction cost in production. Thus, this study is focused on the combination of bottom ash and glass fibre to determine the performance between these two particular materials in concrete. 25% of bottom ash content as fine aggregate replacement by weight had been used in 1% of glass fibre reinforced concrete (GFRC) beam. The performance of GFRC beam was compared and analysed to Glass Fibre Reinforced Concrete with bottom ash (GFBA) beam in this study for future utilization in the construction industry. The presence of glass fibres has help to improve the strength characteristics of concrete while the presence of bottom ash helps to develop long term strength development and produce an economical concrete. In this study, concrete beam was designed for Grade 30. A total of eight (8) concrete cubes and four (4) reinforced concrete beam specimens had been prepared. The curing stages for concretes had been divided into 7, 14, 28 and 42 days before proceed to the destructive test for determination of its compression and flexural strengths. Based on the compression test result, 25% bottom ash content able to develop a long term strength effect with 1% glass fibres concrete. The result of compressive strength at 42 days has shown an increment of 5.57% when compared with the compressive strength at 28 days with the presence of bottom ash in GFRC. However, GFRC beams have showed greater flexural performance than GFBA beams at an average of 31.88% higher when subjected to the theoretical design performance.